2015
DOI: 10.1186/s13045-015-0153-1
|View full text |Cite|
|
Sign up to set email alerts
|

Long non-coding RNA ANRIL is upregulated in hepatocellular carcinoma and regulates cell proliferation by epigenetic silencing of KLF2

Abstract: BackgroundHepatocellular carcinoma (HCC) is one of the leading causes of cancer-related death, especially in China. And the mechanism of its progression remains poorly understood. Growing evidence indicates that long non-coding RNAs (lncRNAs) are found to be dysregulated in many cancers, including HCC. CDKN2B antisense RNA1 (ANRIL), a lncRNA, coclustered mainly with p14/ARF has been reported to be dysregulated in gastric cancer, esophageal squamous cell carcinoma, and lung cancer. However, its clinical signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
56
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(57 citation statements)
references
References 32 publications
1
56
0
Order By: Relevance
“…In a previous work, the authors found that lncRNA‐ANRIL promoted gastric cancer cell growth partly through epigenetically repressing the expression of miR‐99a/miR‐449a in trans (controlling the targets—mTOR and CDK6/E2F1 pathway) by binding to PRC2, thus forming a positive feedback loop. Although the oncogenic role of ANRIL was also found in some other cancer types, inducing lung cancer , hepatocellular carcinoma , esophageal squamous cell carcinoma , and gastric cancer , the underlying mechanism behind lncRNA‐ANRIL regulation remains elusive. Here, we found that TET2 binds to the promoter of lncRNA‐ANRIL and regulates the expression of lncRNA‐ANRIL and its downstream genes (INK4a, INK4b, and ARF).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous work, the authors found that lncRNA‐ANRIL promoted gastric cancer cell growth partly through epigenetically repressing the expression of miR‐99a/miR‐449a in trans (controlling the targets—mTOR and CDK6/E2F1 pathway) by binding to PRC2, thus forming a positive feedback loop. Although the oncogenic role of ANRIL was also found in some other cancer types, inducing lung cancer , hepatocellular carcinoma , esophageal squamous cell carcinoma , and gastric cancer , the underlying mechanism behind lncRNA‐ANRIL regulation remains elusive. Here, we found that TET2 binds to the promoter of lncRNA‐ANRIL and regulates the expression of lncRNA‐ANRIL and its downstream genes (INK4a, INK4b, and ARF).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple long‐chain non‐coding RNA (TUG1, ANRIL, XIST and ZFAS1) and miRNA (miR‐9) can regulate KLF2 expression. Although the function of KLF2 in liver cancer has not been directly investigated and reported, relevant studies have indicated that long‐chain non‐coding RNA such as TUG1 and ANRIL can promote the occurrence of liver cancer and development by apparent silencing of KLF2 expression . Such studies all indicate that KLF2 can negatively regulate liver cancer occurrence and development.…”
Section: Introductionmentioning
confidence: 99%
“…KLF2 is downregulated in gastric cancer, liver cancer, non-small-cell lung cancer and pancreatic ductal adenocarcinoma. [23][24][25] Multiple long-chain noncoding RNA (TUG1, ANRIL, XIST and ZFAS1) and miRNA (miR-9) can regulate KLF2 expression [23][24][25][26][27][28] . Although the function of KLF2 in liver cancer has not been directly investigated and reported, relevant studies have indicated that long-chain non-coding RNA such as TUG1 and ANRIL can promote the occurrence of liver cancer and development by apparent silencing of KLF2 expression.…”
mentioning
confidence: 99%
“…Recently, research suggests that lncRNAs are important in complicated diseases such as cancer [22]. Several lncRNA have been identified as being involved in the development and progression of HCC, such as lncRNA-HEIH [23], HOTAIR [24, 25], lncRNA MVIH [26], lncRNA-Dreh [27], HOTTIP/HOXA13 [28, 29], URHC [30], PCNA-AS1 [31], UFC1 [32], HULC [33], CCAT1 [34], PVT1 [35], ANRIL [36, 37], ZEB1-AS1 [38], PANDAR [39], DANCR [40]. Some of these lncRNA were also identified in our microarray data.…”
Section: Discussionmentioning
confidence: 99%